Native American Adoption, Captivity, and Slavery in Changing Contexts - Carocci, M.; Carocci, M.; Pratt, S.; Pratt, S. (Studies of the Americas, 2012)
Radically rethinks the theoretical parameters through which we interpret both current and past ideas of captivity, adoption, and slavery among Native American societies in an interdisciplinary perspective. Highlights the importance of the interaction between perceptions, representations and lived experience associated with the facts of slavery.